ANALISIS KADAR GLUKOSA DARAH LANSIA YANG MENGIKUTI SENAM LING TIEN KUNG DIBANDINGKAN NILAI STANDAR: Pengaruh Senam Ling Tien Kung Terhadap Penurunan Kadar Glukosa Darah Pada Lansia - Andyanita Hermawati; Anis Murniati; Intan Munawaroh (Jurnal Keperawatan Terapan, 2026)
Impaired blood glucose regulation is frequently observed in older adults and contributes to an increased risk of metabolic complications. Ling Tien Kung is a form of low-intensity physical exercise that has potential benefits in supporting glycemic control among the elderly. This study aimed to examine blood glucose levels in elderly individuals who regularly participate in Ling Tien Kung exercise and to assess their deviation from established standard values. A quantitative observational analytic design with a single-group approach was employed. Twenty-four elderly participants were recruited using purposive sampling. Blood glucose measurements were obtained using a calibrated glucometer. Data analysis was conducted using the One-Sample Wilcoxon test. The mean blood glucose level was 112.08 mg/dL. The results demonstrated a statistically significant difference between the observed blood glucose levels and the standard reference value (p = 0.008). These findings suggest that blood glucose levels among elderly individuals practicing Ling Tien Kung differ significantly from standard values. Ling Tien Kung exercise may play a role in blood glucose regulation in older adults. Further research with controlled designs is recommended